Alteration of the structural properties of inulin gels. (April 2019) - Beccard, Steffen; Bernard, Jörg; Wouters, Rudy; Gehrich, Karin; Zielbauer, Birgitta; Mezger, Markus; Vilgis, Thomas A.
Abstract: In this work, inulin particle gels, prepared with a type of long chain inulin, were examined in terms of their structural properties and mechanical response, depending on the applied shear rates and temperature during gel preparation. The results are interpreted on the basis of a particle gel model, which takes into account the varying gel structure, depending on the sample preparation parameters. X-ray measurements of the inulin powder, used for the experiments, revealed a mostly amorphous powder. The temperature profiles for the sample preparation, chosen from 25 °C to 60 °C with constant stirring at 600 rpm, yielded viscoelastic particle gels with decreasing hardness. By application of high shear rates (7000 rpm) at the same temperature conditions, the gel hardness was increased. Time resolved X-ray scattering experiments during gel formation provided information about the crystallization kinetics and examination of the inulin gels, using static light scattering, confirmed that the final gel particle size depends on the sample preparation temperature. Thus, the results show a high sensitivity of the structural and textural properties of inulin gels to the variation of applied temperature and shearing during sample preparation. Those findings allow the controlled alteration of large scale structures and thus of the textural properties in food systems containing inulin. Graphical abstract: Highlights: Amorphous inulin powder recrystallizes during gel formation. Inulin-water suspensions form particle gels. The texture of the inulin gels is influenced by the variation of temperature and shear rate during sample preparation.